Qili Qiangxin Capsule Combined With Sacubitril/Valsartan for HFrEF: A Systematic Review and Meta-Analysis - Xiang, Qian; Wang, Mengxi; Ding, Yuhan; Fan, Manlu; Tong, Huaqin; Chen, Jiandong; Yu, Peng; Shen, Le; Chen, Xiaohu (Frontiers in Pharmacology, 2022)
Background: HF with reduced ejection fraction (HFrEF) is a complex, chronic disease responsible for many deaths worldwide. ARNI drugs represented by sacubitril/valsartan are the key drugs for the treatment of HFrEF in western medicine, and Qili Qiangxin Capsule (QQC) is a vital drug for the treatment of HFrEF in Chinese medicine. In recent years, there have been many relevant clinical studies on the combination of the two in the treatment of HFrEF. There is a need for evaluating the effectiveness and safety of sacubitril/valsartan combined with QQC for the treatment of HFrEF. Objective: To systematically assess the safety and effectiveness of QQC combined with sacubitril/valsartan in the treatment of HFrEF through a meta-analysis. Methods: Searched the studies of the combination of QQC and sacubitril/valsartan in the treatment of HFrEF, from databases like PubMed, Cochrane Library, Web of Science, prior to October 31, 2021. Two reviewers respectively regulated research selection, data extraction, and risk of bias assessment. And Review Manager Software 5.4 was used for meta-analysis. Results: There were 75 studies pertaining to 2571 patients included. The meta-analysis showed the combination therapy have significant advantages in improving the clinical efficacy, 6-MWT and reducing adverse events (OR=3.54, 95% CI: 2.73 to 4.60, MD=68.04, 95%CI: 23.31 to 112.77, and OR=0.43, 95%CI:0.26 to 0.70, respectively), superior in ameliorating the LVEF, LVEDD, LVESD and SV (LVEF: MD=5.35, 95%CI:4.70 to 6.00, LVEDD:MD=-4.35, 95% CI: -6.06 to -2.63, LVESD: MD=-3.48, 95% CI: -4.45 to -2.52 and SV: MD=5.04, 95% CI: 3.67 to 6.40),and also superior in improving BNP, NT-proBNP,AngⅡ and ALD (MD=-97.55, 95% CI: -112.79 to -82.31, MD=-281.49, 95 % CI: -352.79 to -210.20, MD=-11.48, 95% CI: -15.21 to -7.76 and MD=-26.03, 95 % CI: -38.91 to -13.15), and all the differences have statistical advantages (p<0.05). There is no advantage in improving CO (MD=0.66, 95% CI: -0.12 to 1.43), and the difference has statistical advantages (p<0.05). Conclusions: Compared with the control group, QQC combined with sacubitril/valsartan may be effective in the treatment of HFrEF. However, the conclusion of this study must be interpreted carefully due to the high risk and ambiguity of bias in the included trials.